The volunteering of older people: the cross European vision - SARDINHA, BOGUSLAWA MARIA BARSZCZAK (2011)
The volunteering is one of the very important human activities which depend on many factors. Social political cultural and economical activity influences the levels of volunteering in the countries. On the western economies the volunteering have gain the significance with increasing tendency to enlarge it in the future. This activity is seems to have particular importance for the older people. They usually have more time, most of them are retire and their volunteering work is, fundamental support for the many volunteering organization. The objective of this paper is to characterize the older volunteers, identify types of volunteering activities they are enrolled and to explore the differences between the volunteerism in different European countries. The data used on this paper belong to the wave four of integrated World Value Survey.